Aktivitas Enzim Protease dan Lipase Viscera Ikan Kembung (Restrelliger sp) pada pH Dan Konsentrasi Garam Berbeda - Bustari Hasan; Desmelati Desmelati; Dian Iriani; Titania Nugroho; M Andesba Arifin; Andhra Syatapahana (Berkala Perikanan Terubuk, 2015)
This research was conducted to measure the activity of visceral protease and lipase of mackerel (Rastrelligersp) at different pH and salt concentration. Mackerel, weighing ± 150 g/each were obtained from a fish market in Pekanbaru. Fish weretransported to the laboratory; and at the laboratory, the fish were eviscerated and their visceral organs (intestines, kidneys, liver, spleen, cord, pancreas and gonad) were blended in Tris-HCl buffer and filtered for their crude enzyme extract. The protease activity was measured at pH 6, 7, 8, 9, 10 and 11; and lipase activity was measured at pH2, 3, 4, 5, 5.5, 6, 7, 8, 9, 10 and 11. The protease and lipase activity werealso measured atsalt concentration 0%, 3%, 6%, 9%, 12% and 15%. The results showed that the protease and lipase activity varies with pH value and salt concentration. Protease activity at pH 11 (1,610µmol/ml)and salt concentration 6%(0,869 µmol/ml)showed the highest activity; and pH 10 (0,031µmol/ml) and salt concentration 15% (0,073µmol/ml) was the lowest activity. Lipase activity at pH 4 (2,428 µmol/ml) and salt concentration 3% (4,131µmol/ml) was the highest activity; and pH 11 (0,042µmol/ml) and salt concentration 15% (2,237µmol/ml) was the lowest activity. The protease and lipase activity were decreased withthe increasing of salt concentration.